Comparative Antiscabies Efficacy of Sonneratia alba Extracts: Evaluation of Plant Parts and Concentrations in Mice - Maretha, Delima Engga; Taresha, Lara Mukti; Yuliana, Karina; Ariska, Iis; Lestari, Silvia Diah (Makara Journal of Science, 2026)
This study evaluated the antiscabies efficacy of 70% ethanol extracts from various parts of the mangrove Sonneratia alba (leaves, flowers, bark, and roots) as a potential alternative therapy. The primary objective was to compare the healing effects of the extracts at different concentrations on scabies lesions in mice (Mus musculus). Using a completely randomized design, 24 male Swiss Webster mice were assigned to four groups: a control (K0) group and three treatment groups to receive 10% (K1), 20% (K2), and 30% (K3) extract concentrations topically twice daily. The results demonstrated that the S. alba extracts had significant effects on lesion healing (p < 0.05). The leaf and root extracts exhibited optimal efficacy at a 10% concentration, whereas the bark and flower extracts were the most effective at 30% concentration. These findings suggest that S. alba extracts, particularly those from leaves and roots, hold significant promise as a novel plant-based treatment for scabies, warranting further research into their potential clinical applications.